The influence of cations on biofilm formation of Listeria monocytogenes persistence strains : a thesis presented in partial fulfilment of the requirements for the degree of Doctor of Philosophy in Food Technology, Institute of Food Science and Technology, Massey University, Manawatū, New Zealand - Chalke, Saili (Massey University, 2024)
Listeria monocytogenes is a Gram-positive pathogen, that possess a considerable risk to the human health with a high mortality rate. The persistence of pathogens through severe environmental conditions could be associated with their biofilm forming abilities. In this study, four different L.monocytogenes isolates from the seafood industry, were examined for their biofilm formation ability in the presence of three the cations: magnesium, calcium and sodium that are readily available in the seafood industry. Out of four the two isolates 15G01 and 33H04, were the persistent isolates from different seafood industry in New Zealand. Isolate 15A04 was a low biofilm former and the last isolate 16A01 was associated with a mussel contamination outbreak. The divalent cations, magnesium and calcium had a significantly greater effect on biofilm formation compared to the monovalent cation, sodium, especially at a concentration of 50mM. To further understand the effect, comparative transcriptomics was used on L.monocytogenes isolate 15G01 (a persistent and high biofilm forming isolate) and 15A04 (a low biofilm former). Both the isolates were exposed to 50mM concentrations of magnesium and sodium. In the presence of magnesium, various genes related to the phosphotransferase system, flagellar assembly, chemotaxis and various signal transduction receptors were upregulated. In case of sodium, the results indicated limited effect on gene expression for both the isolates. As biofilm is a community of bacteria enclosed in a self-induced matrix called EPS (extracellular polymeric substances), understanding the influence of cations on the composition of the EPS and the structural stability of biofilm is important. Magnesium enhanced the polysaccharide content, thus enhancing biofilm formation particularly in 15G01. eDNA concentration increased in the presence of cations however there were no significant differences among the cations. A unique hexagonal structure with voids were observed for the first time in the presence of magnesium and calcium for isolate 15A04. These findings contribute insights into the role of cations in biofilm formation, their involvement in regulating the complex network in biofilms and maintaining their structural integrity.
Keywords: listeria monocytogenes, biofilm, cations, magnesium, calcium, sodium; Listeria monocytogenes; Cations; Biofilms; Seafood; Contamination; 310701 Bacteriology; 300607 Food technology